Juridical Analysis of Hospital Liability for Medical Malpractice - C.Winata; D.Hartono (International Medical Journal Corp. Ltd, 2025)
Introduction: Medical malpractice remains a critical intersection of healthcare and law, where patient injuries demand accountability from healthcare institutions. While physicians are historically the focus of negligence claims, modern legal frameworks increasingly hold hospitals directly liable for systemic failures and corporate negligence. Methods: This study employs a normative juridical research method, analyzing statutory regulations, judicial precedents, and legal doctrines governing hospital liability. It examines how corporate negligence and vicarious liability apply to medical malpractice within institutional healthcare settings. Results: The findings reveal that hospital liability is no longer limited to vicarious liability for employee actions under doctrines like respondeat superior. Instead, contemporary jurisprudence recognizes independent corporate liability, establishing that hospitals owe an absolute duty of care directly to patients regarding staff credentialing, equipment maintenance, and operational safety protocols. Discussion: The literature review demonstrates a significant shift from localized, practitioner-focused fault toward a comprehensive institutional risk-management paradigm. Scholars emphasize that systemic vulnerabilities often underlie clinical errors, requiring hospitals to maintain strict internal oversight. The discussion contrasts strict liability with fault-based liability, highlighting the evolving standard of care required to balance operational efficiency with patient protection. Conclusions: This research concludes that hospitals bear a dual layer of liability—both indirect for personnel misconduct and direct for institutional negligence. To minimize legal exposure and elevate patient safety, hospitals must enforce stringent peer-review mechanisms and continuous risk audits.